CRIANÇAS E ADOLESCENTES EM CUIDADOS PALIATIVOS ONCOLÓGICOS: a intervenção do Serviço Social junto às suas famílias - Tatiana Silva Camara da Silva (Universidade Federal do Maranhão, 2010)
This study aims to discuss and support the activities of social workers in social services that assist children and adolescents with cancer, as well as their families, in palliative care. It also aims to contribute to teaching and research in the area. Based on a literature review, the article discusses the following lines of analysis: the role of Social Work and health care for families, features of childhood cancer and palliative care and how illness and death in childhood represent a tragedy for their families. It is necessary to understand who these families are, and how the impacts brought by the current economic system affect the relations among it ́s members during the time of treatment. Considering this background, there are challenges for Social Work, such as the integration of social policies for intervention in health care as well as streightening Social Workers Professional activity and also putting into practice Political and Ethical Projects in interdisciplinary practices. Considering these highlights some activities for professional intervention were proposed in the end of the paper.